2016
DOI: 10.1242/bio.019711
|View full text |Cite
|
Sign up to set email alerts
|

Adamts18 deletion results in distinct developmental defects and provides a model for congenital disorders of lens, lung, and female reproductive tract development

Abstract: The ADAMTS family comprises 19 secreted metalloproteinases that cleave extracellular matrix components and have diverse functions in numerous disease and physiological contexts. A number of them remain ‘orphan’ proteases and among them is ADAMTS18, which has been implicated in developmental eye disorders, platelet function and various malignancies. To assess in vivo function of ADAMTS18, we generated a mouse strain with inactivated Adamts18 alleles. In the C57Bl6/Ola background, Adamts18-deficient mice are bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Mammary gland development in Adamts18 −/− mice. To assess the functional importance of Adamts18 in mammary gland development, we generated mice homozygous for an allele lacking exons 8 and 9, which encode the Zn-binding catalytic site 31 and analyzed their inguinal mammary glands at critical developmental stages by whole mount stereomicroscopy. In prepubertal, 14-dayold WT and Adamts18 −/− littermates, the ductal system was rudimentary and of similar size in both genotypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammary gland development in Adamts18 −/− mice. To assess the functional importance of Adamts18 in mammary gland development, we generated mice homozygous for an allele lacking exons 8 and 9, which encode the Zn-binding catalytic site 31 and analyzed their inguinal mammary glands at critical developmental stages by whole mount stereomicroscopy. In prepubertal, 14-dayold WT and Adamts18 −/− littermates, the ductal system was rudimentary and of similar size in both genotypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, targeting downstream Wnt signaling has potential side effects because this signaling pathway is physiologically important for stem cells in many tissues. Based on the mouse model, ADAMTS18 is important for development of specific organs but it does not appear to have an essential function in adult mice 31 . Furthermore, in its extracellular location ADAMTS18 makes it an excellent target for antibody-mediated therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The modulators matrix metalloproteinases (MMPs) family plays critical roles in the TGFβ2-mediated matrix contraction. [26][27][28] Besides, MMP2 is closely correlated with the proliferation of lens epithelial cells. Therefore, lncRNA PVT1 could regulate the HLE B-3 cell biological activity via modulating the MMP2.…”
Section: Discussionmentioning
confidence: 99%
“…In C57Bl6/Ola mice, Adamts18 deletion results in distinct developmental defects, including congenital disorders of the lens, lung, and female reproductive tract development. 29 In humans, ADAMTS18 mutations have been linked to tumorigenesis, 30 eye diseases, 31e33 reduced bone mineral density formation, 34 and white matter integrity of the brain. 35 We have previously reported that ADAMTS18 is associated with platelet lyses and cerebral infarction in a postischemic stroke model.…”
mentioning
confidence: 99%